Teacher’s Efforts to Prevent Bullying at Madrasah Ibtidaiyah - Marlini, Marlini; Tanjung, Salis Alvisyhari; Andhika, M. Rezki; Suharman, Suharman (Jurnal Ilmiah Teunuleh, 2026)
This study aims to describe the efforts of teachers and the principal in preventing bullying at Madrasah Ibtidaiyah (MI) 10 Layung, Aceh Barat Regency. The research employed a qualitative approach with a descriptive design. The informants consisted of the school principal, classroom teacher, and three students selected through purposive sampling. Data were collected through interviews, observations, and document analysis, then analyzed using an interactive analysis model consisting of data reduction, data display, and conclusion drawing. The findings show that bullying cases at MI 10 Layung are relatively low and continue to decline. The principal emphasizes direct guidance for both perpetrators and victims, as well as involving parents in more serious cases. Classroom teachers handle minor incidents through quick and consistent educational reprimands, including the strategy of calling students by their parents’ names to create a deterrent effect. Observations support the interview results, indicating that the school environment is safe, student interactions are positive, and teachers actively supervise and guide students. The study concludes that the synergy among the principal, teachers, students, and parents plays an essential role in creating a conducive learning environment and preventing bullying in primary schools.